2020
DOI: 10.1371/journal.pone.0239009
|View full text |Cite
|
Sign up to set email alerts
|

Building a green Belt and Road: A systematic review and comparative assessment of the Chinese and English-language literature

Abstract: International attention on the environmental impacts of China's Belt and Road Initiative (BRI) is increasing, but little is known internationally about the large corpus of Chinese BRI environmental research. We present the first systematic review of the Chinese and Englishlanguage BRI environmental research, supported with text mining and sentiment analysis. We found that the research is dominated by Chinese authors writing about BRI routes within China in Chinese, even though concerns around BRI are largely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…Earlier studies have also attempted to quantify the importance of non-English-language scientific knowledge in ecological evidence syntheses. For example, 67% of the scientific literature identified in a systematic review on Japanese bats including many endemic and threatened species was in Japanese [61], literature searches in Spanish increased the amount of scientific literature on interactions between birds and wind farms by 11% [62], and 65% of the literature included in a systematic review on China’s Belt and Road Initiative, a continental-scale infrastructure development that potentially has disastrous consequences for biodiversity in the region, was in Chinese [63]. Despite the importance of their findings, most studies are limited only to a specific research topic and a single non-English language, restricting the generalizability of their findings.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Earlier studies have also attempted to quantify the importance of non-English-language scientific knowledge in ecological evidence syntheses. For example, 67% of the scientific literature identified in a systematic review on Japanese bats including many endemic and threatened species was in Japanese [61], literature searches in Spanish increased the amount of scientific literature on interactions between birds and wind farms by 11% [62], and 65% of the literature included in a systematic review on China’s Belt and Road Initiative, a continental-scale infrastructure development that potentially has disastrous consequences for biodiversity in the region, was in Chinese [63]. Despite the importance of their findings, most studies are limited only to a specific research topic and a single non-English language, restricting the generalizability of their findings.…”
Section: Supporting Informationmentioning
confidence: 99%
“…They found that the accuracy of the dictionary-based method depended on the comprehensiveness of the selected emotional dictionary. A systematic review and comparative assessment of the Chinese and English-language literature on the environmental impacts of China's BRI (Teo et al 2020) found that much of the Chinese literature may be targeted for domestic consumption and thus may not contribute to the international discourse on BRI. A paper by Chandra et al (2020) that aimed to extract the sentiments of the BRI from Twitter found positive sentiments dominant among the extracted tweets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature has focused on a number of different issues involving a range of disciplines including international relations, politics, economics, geography, management, and environmental studies. Issues discussed include the drivers that led to the adoption of the BRI (Cai, 2017; Johnston, 2019; Swaine, 2015; Yu, 2017); the impact on global governance (Carrai et al, 2020; Chun, 2017); the political implications in terms of the expansion of Chinese influence and “soft power” (Schaffer, 2021; Voon and Xu, 2020); and the environmental consequences of BRI infrastructure projects (Ascensão et al, 2018; Teo et al, 2019, 2020).…”
Section: China's Brimentioning
confidence: 99%